Adoption and impact of OER in the Global South - Project Muse; Project Muse. (Project Muse, 2018)
Education in the Global South faces several key interrelated challenges, for which Open Educational Resources (OER) are seen to be part of the solution. These challenges include: unequal access to education; variable quality of educational resources, teaching, and student performance; and increasing cost and concern about the sustainability of education. The Research on Open Educational Resources for Development (ROER4D) project seeks to build on and contribute to the body of research on how OER can help to improve access, enhance quality and reduce the cost of education in the Global South. This volume examines aspects of educator and student adoption of OER and engagement in Open Educational Practices (OEP) in secondary and tertiary education as well as teacher professional development in 21 countries in South America, Sub-Saharan Africa and South and Southeast Asia. The ROER4D studies and syntheses presented here aim to help inform Open Education advocacy, policy, practice and research in developing countries.
section 1. Overview -- 1. Research on Open Educational Resources for Development in the global south : project landscape -- 2. Factors influencing open educational practices and OER in the global south : meta-synthesis of the ROER4D project -- 3. OER use in the global south : a baseline survey of higher education instructors -- section 2. South America -- 4. Open access and OER in Latin America : a survey of the policy landscape in Chile, Colombia and Uruguay -- 5. Co-creation of OER by teachers and teacher educators in Colombia -- 6. Effectiveness of OER use in first-year higher education students' mathematical course performance : a case study -- section 3. Sub-Saharan Africa -- 7. Tracking the money for open educational resources in South African basic education : what we don't know -- 8. Teacher educators and OER in East Africa : interrogating pedagogic change -- 9. Factors shaping lecturers' adoption of OER at three South African universities -- 10. OER in and as MOOCs -- section 4. South and Southeast Asia -- 11. Cultural-historical factors influencing OER adoption in Mongolia's higher education sector -- 12. Higher education faculty attitude, motivation and perception of quality and barriers towards OER in India -- 13. Impact of integrating OER in teacher education at the Open University of Sri Lanka -- 14. Teacher professional learning communities : a collaborative OER adoption approach in Karnataka, India -- 15. An early stage impact study of localised OER in Afghanistan -- section 5. Conclusion and recommendations -- 16. OER and OEP in the global south : implications and recommendations for social inclusion.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Education, Higher -- Effect of technological innovations on -- Developing countries; Electronic information resources -- Developing countries; Open access publishing -- Developing countries; Internet in education -- Developing countries; Electronic books; Electronic books